VITAMIN D3 IN THE PATHOGENESIS AND CLINICAL COURSE OF MULTIPLE SCLEROSIS: A COMPREHENSIVE REVIEW OF CURRENT EVIDENCE (2015–2026) - Martyna Jaciubek; Maja Osuch; Maciej Osuch; Olga Tatarata; Carmena Luty; Amanda Abramowicz; Magdalena Rumin; Anna Kiełboń; Zuzanna Olga Reklewska; Kornelia Domagała (International Journal of Innovative Technologies in Social Science, 2026)
Multiple sclerosis (MS) is a chronic immune-mediated demyelinating disease of the central nervous system characterized by inflammatory activity, neuroaxonal degeneration, and progressive neurological disability. Over the past decade, converging epidemiological, genetic, and mechanistic evidence has positioned vitamin D3 as a biologically plausible environmental determinant influencing MS susceptibility and potentially modulating disease course. This comprehensive review synthesizes peer-reviewed literature published between 2015 and 2026, including Mendelian randomization analyses, large-scale genomic studies, randomized controlled trials, and contemporary meta-analyses. Independent Mendelian randomization studies consistently demonstrate that genetically determined lower circulating 25-hydroxyvitamin D concentrations increase the risk of MS, supporting a causal role in disease susceptibility. In contrast, randomized supplementation trials in established relapsing–remitting MS report heterogeneous and generally modest effects on relapse rates, MRI activity, and disability progression. Emerging data from early-stage disease, including clinically isolated syndrome, suggest a potential stage-dependent benefit. Collectively, current evidence indicates that vitamin D functions primarily as a susceptibility modifier and early immunological regulator rather than a definitive disease-modifying therapy in established MS. Future research should prioritize early-life exposure, genotype-informed stratification, and long-term clinical outcomes to clarify the translational potential of vitamin D optimization in multiple sclerosis.